The Evaluation on Thermal Performance of Rumah Negeri Sembilan Berserambi Dua dan Beranjung (International Journal of Built Environment and Sustainability, 2023)
Traditional Malay house, a passive design architecture, is believed to have more effective thermal performance than modern residential houses through climatic design strategies. Unfortunately, the Malay house has experienced numerous changes and is confronted with constant dangers due to present-day science and innovation. Thus, this study aimed at evaluating the thermal performance of rumah Negeri Sembilan berserambi dua dan beranjung for sustainable practice in the tropical environment. The method used was fieldwork: observation and thermal measurement. Comparing the suggested comfort level by ASHRAE 55 and ICOP, 20% percent of the total data is falls within the thermal comfort range suggested. However, the house is considered in comfort environment between 25-27ºC, which is only in the early morning. As for the wind flow, each house division recorded different readings. However, it was still within the comfort level range, i.e., between 0.12-1.25m/s, while the RH level was 50-60%. Therefore, the primary findings elaborate that the Malay house construction has five factors that directly influence the house's thermal performance. These include floor areas, openings, floor and roof heights, materials, open compound areas, and building setting. This study aspires to provide useful insights regarding the effectiveness of practices in the climatic design strategies of a traditional Malay house. Thus, its contribute to the scientific discussions on sustainable practices in modern residential design which aligned with the Twelfth Malaysia Plan (RMK12) Theme 3.
Keywords: Climatic design strategies, Malay house, passive design, sustainable practice, thermal performance